The Impact of Data-Driven Planning on Teacher Resilience: The Mediating Role of Team Collaboration - Tia Ningrum; Anisah Anisah; Fifin Wildanah; Nikmah Hayati; Irsyad; Aini Septia Rahmalita; Mahaliza Mansor (Indonesian Journal of Learning Education and Counseling, 2026)
This study aims to examine the effect of data-driven planning on teachers’ resilience through team collaboration in vocational high schools. This study addresses the limited empirical evidence linking data-driven planning to teacher resilience, particularly through collaborative mechanisms. Using quantitative research design, data were collected through a structured questionnaire administered to 482 teachers’ senior high schools in West Sumatra, selected using the proportional stratified random sampling technique. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PL S-SEM) to test both direct and indirect relationships among variables, with reliability assessed through Cronbach’s alpha and composite reliability, and validity evaluated using Average Variance Extracted (AVE).  Data-driven planning is conceptualized as the systematic use of data for instructional and managerial decision-making, team collaboration as structured professional interaction among teachers, and teacher resilience as the ability to adapt and sustain performance under challenges.The findings indicate that data-driven planning has a positive and significant effect on team collaboration, collaboration has a strong positive effect on teacher resilience, and collaboration significantly mediates the relationship between data-driven planning and resilience. These findings highlight the critical role of collaborative practices as a mechanism linking planning processes to resilience outcomes.This study contributes to the existing literature on educational management by integrating data-driven planning, collaboration, and resilience into a single empirical model. Practically, the results suggest that schools should strengthen collaborative data use to enhance teacher resilience.